Rahn Emas dalam Fatwa DSN-MUI : (Analisis Hadis dan Praktik di Pegadaian Syariah Cabang Sampang) - Fitriyana Agustin Fifin; Putri Alfia Halida (El Nubuwwah Jurnal Studi Hadis, 2025)
This study investigates the implementation of gold-based pawning (rahn) at Pegadaian Syariah Sampang through the lens of Prophetic hadith and the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) No. 25/DSN-MUI/III/2002 on Rahn. The central issue addressed is the extent to which the rahn contract, including gold valuation mechanisms and the resolution of non-performing financing, aligns with core Islamic legal and ethical principles. Employing a qualitative-descriptive method supported by a Systematic Literature Review (SLR), this research incorporates both textual analysis of canonical hadith and empirical field interviews. The findings demonstrate that rahn is legally valid and normatively grounded in multiple authentic narrations (á¹£aá¸¥Ä«á¸¥) of the Prophet Muhammad ï·ºâ€”particularly from Bukhari and Muslimâ€”supported by classical scholars such as al-â€˜AynÄ«, al-QÄrÄ«, and al-á¹¢anâ€˜ÄnÄ«. The procedural implementation at Pegadaian Syariah Sampang adheres to the essential components of the rahn contract, encompassing administrative protocols, digitalized gold appraisal based on karat weight, and disbursement through an integrated system. The determination of loan value (marhÅ«n bih), administrative cost (muâ€™nah), and contractual execution complies with the principles of justice (Ê¿adl), transparency (wuá¸Å«á¸¥), and the avoidance of ribÄ, reflecting the maqÄá¹£id al-sunnah (higher objectives of the Prophetic Sunnah). Non-performing loans are addressed through structured mechanisms such as rescheduling, reconditioning, restructuring, persuasive negotiation, and, where necessary, collateral execution. The study concludes that the rahn practice at Pegadaian Syariah Sampang is in substantial conformity with Islamic legal ethics and contemporary fatwas, though greater efforts in consumer education, sharia compliance monitoring, and institutional governance are necessary to ensure long-term sustainability and maslahah (public benefit). This research contributes both to theoretical discourse in Islamic jurisprudence and practical policy-making in grassroots Islamic finance.